Development of degradable networked-organic semiconductors and effects on charge carrier mobility in organic thin-film transistors - Jin, Hyunjung; Kim, Kyeongmin; Kim, Kyuyeon; Park, Sungmin; Shin, Eul-Yong; Heo, Jae Won; Lee, Hyunjoo; Baek, Se-Woong; Kim, In Soo; Ahn, Hyungju; Son, Hae Jung (Royal Society of Chemistry, 2024)
As a promising solution to address the growing concern of electronic waste, transient electronics, such as biomedical implants, environmental sensors, and hardware-secured devices, have garnered considerable attention. These devices can be engineered to exhibit partial solubility, degradability, or physical dissolution. For the development of degradable transient organic electronics, it is important to develop degradable polymeric organic semiconductors. However, few studies have focused on controlling the degradation rates of polymers in films. In this study, we designed and synthesized three different degradable polymers, namely, PY-m-TIPO, PY-p-TIPO, and PY-t-TIPO, through in situ polymerization in the film state. Notably, PY-t-TIPO exhibited a significantly higher charge mobility of 1.67 × 10？3 cm2 V？1 s？1 in organic thin-film transistors (OTFTs) than PY-m-TIPO and PY-p-TIPO although all the degradable polymer films exhibited similar amorphous properties. We demonstrated that the number of bonding arms affects not only the degradation rate of the polymer films but also the charge mobility of the corresponding OTFTs. Our study provides design guidelines for developing degradable polymers with controllable degradation rates for high charge mobility in transient OTFTs.